ANALYSIS OF ECONOMIC OBSTACLES AND STRATEGIES FOR THE FIRST PUMPED STORAGE HYDROPOWER PLANTS IN INDONESIA: A CASE STUDY OF UPPER CISOKAN HYDROPOWER PLANTS - Grace Meitrin Panjaitan; Mirwan Surya Perdhana (Jurnal Apresiasi Ekonomi, 2025)
TThis study aims to analyze economic barriers and formulate strategies for developing the first Pumped Storage Hydroelectric Power Plant in Indonesia, focusing on a case study of the Upper Cisokan Pumped Storage Hydroelectric Power Plant under PT PLN (Persero). This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews with officials and employees of PT PLN (Persero) Central Java Development Unit (UIP JBT) who were directly involved in the project. Data analysis methods include data reduction, coding, and data presentation. Conclusions are drawn in a descriptive narrative manner.The results of the study indicate that the main obstacles in the development of the Upper Cisokan hydropower plant include economic factors, such as the complexity of project funding involving administrative requirements and financial commitments from various parties. In addition, technical obstacles were also found, especially related to the dynamics of changes in construction design due to external factors such as geological conditions and government regulations. Based on these findings, this study proposes a development strategy that includes optimizing project governance, diversifying financing sources, and increasing collaboration between stakeholders to support the sustainability of the Upper Cisokan hydropower plant development.Keywords: Obstacles, Challenges, Economic Aspects and Upper Cisokan Pumped Storage Hydroelectric Power Plant